Immunodeficiencies and pathologies associated with mutations in STIM/ORAI - Capiod, Thierry (Henry Stewart Talks, 2012)
STIM/Orai, two major molecular components of the calcium entry pathways observed in all tissues and associated to several physiological functions, Mutations causing immunodeficiencies and cancer by altering calcium homeostasis.